2019
DOI: 10.3389/fcimb.2019.00384
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Recovered From Olive Trees (Olea europaea) in Turkey Reveal Allopatry With African and South American Lineages

Abstract: Cryptococcus species are life-threatening human fungal pathogens that cause cryptococcal meningoencephalitis in both immunocompromised and healthy hosts. The natural environmental niches of Cryptococcus include pigeon (Columba livia) guano, soil, and a variety of tree species such as Eucalyptus camaldulensis, Ceratonia siliqua, Platanus orientalis, and Pinus spp. Genetic and genomic studies of extensive sample collections have provided insights into the population distribution and composition of different Cryp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
1
11
0
1
Order By: Relevance
“…Regarding genotypes, C. gattii VGII is the most common in clinical isolates, while the VGIII genotype is less frequent [ 102 ]. However, in the study by Escandon et al, the most common phenotype determined in environmental isolates was VGIII, in agreement with the results reported by Firacative et al in 2011, although to a lesser extent [ 26 , 57 ]. Additionally, the predominant genotype for clinical isolates of C. neoformans is VNI [ 102 , 103 ], which coincides with the genotype determined in environmental samples [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding genotypes, C. gattii VGII is the most common in clinical isolates, while the VGIII genotype is less frequent [ 102 ]. However, in the study by Escandon et al, the most common phenotype determined in environmental isolates was VGIII, in agreement with the results reported by Firacative et al in 2011, although to a lesser extent [ 26 , 57 ]. Additionally, the predominant genotype for clinical isolates of C. neoformans is VNI [ 102 , 103 ], which coincides with the genotype determined in environmental samples [ 18 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the C. neoformans complex has been reported in tree species, with higher prevalence compared to the C. gattii complex, for example in Eucalyptus spp. [ 55 , 56 ], Terminalia catappa [ 22 ], Olea europea [ 57 ], and Ceratonia (carob tree) [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the improvement of sequencing technologies and bioinformatics tools allowed analysis of whole-genome sequences, revealing new details in the structure and global geographical distribution of the Cryptococcus populations together with the identification of additional clades and subclades ( Farrer et al 2019 ). Most of these studies focused on C. neoformans , with >1000 C. neoformans genome sequences analyzed in four studies ( Desjardins et al 2017 ; Rhodes et al 2017b ; Vanhove et al 2017 ; Ashton et al 2019 ; Ergin et al 2019 ). Through these efforts, the VNB clade has been separated into the VNBI and VNBII subclades, which have different resistance to oxidative stress and a different ability to produce melanin ( Desjardins et al 2017 ; Vanhove et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the closely related species Cryptococcus gattii [11], responsible for the Vancouver Island (BC, Canada) outbreak of cryptococcosis in 1999, is documented to be associated with the bark of a variety of tree species (potentially over 50) [12]. Several recent studies have also found C. neoformans isolates in association with trees, such as eucalyptus in Egypt [13], and olive in Turkey [14]. (note: at least a dozen such papers) Furthermore, recent work has shown that C. neoformans is able to grow both on live plant material, such as Arabidopsis seedlings and Douglas fir trees, as well as in saprobic association with dead plant materials [15].…”
Section: Introductionmentioning
confidence: 99%